RETRACTED: Molecular Perspectives of Mitophagy in Myocardial Stress: Pathophysiology and Therapeutic Targets - Ji, Haizhe; Wu, Dan; Kimberlee, O’Maley; Li, Ruibing; Qian, Geng (Frontiers in Physiology, 2021)
A variety of complex risk factors and pathological mechanisms contribute to myocardial stress, which ultimately promotes the development of cardiovascular diseases, including acute cardiac insufficiency, myocardial ischemia, myocardial infarction, high-glycemic myocardial injury and acute alcoholic cardiotoxicity. Myocardial stress is characterized by abnormal metabolism, excessive reactive oxygen species production, an insufficient energy supply, endoplasmic reticulum stress, mitochondrial damage and apoptosis. Mitochondria, the main organelles contributing to the energy supply of cardiomyocytes, are key determinants of cell survival and death. Mitophagy is important for cardiomyocyte function and metabolism because it removes damaged and aged mitochondria in a timely manner, thereby maintaining the proper number of normal mitochondria. In this review, we first introduce the general characteristics and regulatory mechanisms of mitophagy. We then describe the three classic mitophagy regulatory pathways and their involvement in myocardial stress. Finally, we discuss the two completely opposite effects of mitophagy on the fate of cardiomyocytes. Our summary of the molecular pathways underlying mitophagy in myocardial stress may provide therapeutic targets for myocardial protection interventions.